1989
DOI: 10.1017/s0013091500004727
|View full text |Cite
|
Sign up to set email alerts
|

The Borel structure of iterates of continuous functions

Abstract: The set of increasing (= nondecreasing) and decreasing (= nonincreasing) functions in % will be denoted by J and 2, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…First we prove the aforementioned result [1] concerning extending a given function to a square. (g~\x)) whenever x e g (F).…”
Section: Elementary Observationsmentioning
confidence: 89%
See 1 more Smart Citation
“…First we prove the aforementioned result [1] concerning extending a given function to a square. (g~\x)) whenever x e g (F).…”
Section: Elementary Observationsmentioning
confidence: 89%
“…Let C denote the space of continuous functions mapping [0,1] into itself and endowed with the sup metric. It has been shown that C 2 = {f°f:fe C} is an analytic but non-Borel subset of C. This implies that there is no simple geometric characterization for a function being a square.…”
mentioning
confidence: 99%
“…However, the paper [44] by Humke and Laczkowich shows that this set is analytic and non-Borel in C(I, I). Nonexistence of roots is typical also for C 1 -smooth functions with two fixed points which was observed by Weinian Zhang in [182].…”
Section: Vol 87 (2014) Recent Results On Iteration Theory 217mentioning
confidence: 99%
“…And this concerns both the purely set-theoretic case (cf., for instance, [75] by G. Zimmermann, but also [41] by R. E. Rice, B. Schweizer and A. Sklar) and the case of regular mappings, no matter we have in mind the continuity (see [11] by P.D. Humke and M. Laczkovich, [45] by K. Simon, and [4] by A.M. Blokh), or the holomorphicity (cf.…”
Section: Multifunction Casementioning
confidence: 99%